Dual electric fields in Ni-CdS@Ni(OH)2 heterojunction: A synergistic spatial charge separation approach for enhanced coupled CO2 photoreduction and selective toluene oxidation - Khakemin Khan; Ahmed Mahmood Idris; Haseebul Hassan; Sajjad Haider; Salah Ud-Din Khan; Antonio Miotello; Ihsanullah Khan (Advanced Powder Materials)
Simultaneously inducing dual built-in electric fields (EFs) both within a single component and at the heterojunction interface creates a dual-driving force that is crucial for promoting spatial charge separation. This is particularly significant in challenging coupled systems, such as CO2 photoreduction integrated with selective oxidation of toluene to benzaldehyde. However, developing such a system is quite challenging and often requires a precise design and engineering. Herein, we demonstrate a unique Ni-CdS@Ni(OH)2 heterojunction synthesized via an in-situ self-assembly method. Comprehensive mechanistic and theoretical investigations reveal that the Ni-CdS@Ni(OH)2 heterojunction induces dual electric fields (EFs): an intrinsic polarized electric-field within the CdS lattice from Ni doping and an interfacial electric-field from the growth of ultrathin nanosheets of Ni(OH)2 on Ni-CdS nanorods, enabling efficient spatial charge separation and enhanced redox potential. As proof of concept, the Ni-CdS@Ni(OH)2 heterojunction simultaneously exhibits outstanding bifunctional photocatalytic performance, producing CO at a rate of 427 ​μmol ​g−1 ​h−1 and selectively oxidizing toluene to benzaldehyde at a rate of 1476 ​μmol ​g−1 ​h−1 with a selectivity exceeding 85%. This work offers a promising strategy to optimize the utilization of photogenerated carriers in heterojunction photocatalysts, advancing synergistic photocatalytic redox systems.